Monitoring Pertumbuhan Tanaman Hidroponik Berbasis Internet of Things (IoT) - Iwan Fitrianto Rahmad; Aditya Arielevi; Mhei Arni Olivia; Amirul Amin PS; M Fikry Haikal (BEES: Bulletin of Electrical and Electronics Engineering, 2026)
The development of Internet of Things (IoT) technology encourages the implementation of smart agriculture to support real-time, data-based plant environmental monitoring. This research aims to design and implement a monitoring system for temperature, air humidity, and light intensity on bean sprout growth using a DHT11 sensor and an LDR light sensor module integrated with the Arduino IoT Cloud. The system was developed using the System Development Life Cycle (SDLC) method and tested under two bean sprout planting conditions, namely conditions with light and without light. Environmental data was collected automatically for eight days and displayed in graphs and tables on the cloud dashboard. The test results showed that bean sprout planting without light had higher air humidity and environmental conditions more suitable for bean sprout growth compared to planting with light. The developed IoT system is able to monitor environmental conditions accurately, in real time, and continuously, and supports comparative analysis of plant growth based on differences in light intensity.